(untitled) (International Seven Journal of Multidisciplinary, 2024)
Acute respiratory infections (ARIs) are diseases that affect any segment of the respiratory tract for up to 7 days. They are responsible for 25% of all illnesses and deaths among children in developing countries. On average, children in urban areas suffer from 4 to 6 ARIs a year. Approximately 2-3% of ARIs progress to infection of the lung parenchyma, of which 10-20% die. Community-acquired pneumonia (CAP) is the main ARI of the lung parenchyma. CAP is characterized as the presence of signs and symptoms of pneumonia in a previously healthy child, due to an infection contracted outside hospital. Complicated pneumonia is when there is extensive consolidation, abscess, pleural effusion, pneumatocele and atelectasis. Pneumococcal infection is a prevalent cause worldwide and is responsible for significant morbidity and mortality rates, which is evidenced by 800,000 deaths in 2017, resulting in 15% of all deaths of children under 5 in developing countries.In Brazil, this disease is the leading cause of preventable death in childhood.According to data from the Unified Health System in 2017, pneumonia was the second cause of hospitalization in 2017, accounting for 14% of all hospitalizations. In this way, the present study aims to carry out an epidemiological mapping outlining the number of children hospitalized for complicated pneumonia, in order to highlight the epidemiological, individual, physical, socioeconomic and health characteristics of each individual, intervening more effectively to avoid negative outcomes of this disease which is still a serious public health problem in developing countries.